THE DEVELOPMENT OF THE DIGITAL ECONOMY IN THE MILLENNIAL GENERATION - Syahputra, Edy; Hutasuhut, Saidun; Hasyim, Hasyim (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this research is to find out how the development of the digital economy in the millennial generation. The research uses the Systematic Literature Review method in several research websites, journals, databases used to find articles about relevant research. Millennials, who are often in the spotlight, have a significant affinity with the digital world, using digital space as their personal platform to access, acquire and share information found on the internet. The readiness of the millennial generation, compared to previous generations, has proven to be more capable in facing the changing times, especially in the context of technological developments that dominate the digital economy today. Indonesia itself has entered the ASEAN Economic Community (AEC), leading to greater transparency in the movement of resources, products and services. This encourages us to continuously improve our skills and expertise to survive in the ever-evolving digital economy. In the Digital Economy Era, information is no longer just a medium for transactions and communication, but the main source of profit in the economy. The Digital Economy encourages changes in the mindset of individuals and organizations in making economic decisions, especially as a result of the development of the internet and mobile device technology. A wise attitude towards all kinds of promotions of goods and services on the internet, especially from social media influencers, is needed to be owned by every consumer.